EVALUASI IMPLEMENTASI PERATURAN DAERAH KOTA BENGKULU NOMOR 3 TAHUN 2008TENTANG KETENTRAMAN DAN KETERTIBAN UMUM(Studi Penanganan Pedagang Kaki Lima di Pasar Panorama Kota Bengkulu) - Yusron Hanif, Yusron; Yusron Hanif , Yusron; Djonet Santoso; Yorry Hardayani (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
This research aims to identify the causes of the less than optimal implementation of Bengkulu City Regional Regulation Number 3 of 2008 concerning Peace and Public Order (Study of Handling Street Vendors in Panorama Market, Bengkulu City). The method used in this research is descriptive qualitative. This research aspect uses Ripley and Franklin's theory, namely Compliance and What's Happening. The results of this study indicate that there are several factors that cause less than optimal implementation of Bengkulu City Regional Regulation Number 3 of 2008 concerning Peace and Public Order (Study of Handling Street Vendors in Panorama Market, Bengkulu City) in the Compliance aspects are not in accordance with applicable regulations, namely the implementation is not in accordance with SOP and What's Happening aspect, namely: 1) There are no sanctions given to street vendors who sell on the road and sidewalks in accordance with the provisions of the applicable PERDA, 2) the lack of budget for Satpol PP Bengkulu City to carry out routine or periodic control, 3) The existence of thugs and playing apparatus that hinder the implementation process, 4) There is no measure of success in the implementation process carried out by Satpol PP Bengkulu City, 5) Panorama Market which cannot accommodate the increasing number of street vendors, 6) Lack of awareness of street vendors of the Regulation that prohibits selling on sidewalks and road bodies, 7) People who no longer want to shop in the market. The author recommends that it be better to provide a special place or stall for traders where traders then pay a fee for cleaning and security as well as increasing the budget for the Bengkulu City Satpol PP in handling street vendors.